Hepatotoxicity Due to Azole Antimycotic Agents in a HLA B*35:02-Positive Patient - Bühler, Tim; Medinger, Michael; Bouitbir, Jamal; Krähenbühl, Stephan; Leuppi-Taegtmeyer, Anne (Frontiers in Pharmacology, 2019)
We will present a 42 year old woman with acute myeloid leukaemia and pulmonary aspergillosis. She was treated with several antifungal agents, including 3 triazoles. Voriconazole, posaconazole, and isavuconazole all led to hepatocellular liver injury. Voriconazole administration led to a peak alanine aminotransferase (ALT) value of 1793 U/l (normal range 9 – 59 U/l). After posaconazole and isavuconazole treatment, ALT rose over 500 U/l. The typical course of events, exclusion of differential diagnoses, and normalization of the liver function tests (LFTs) after stopping the triazoles were highly suspicious for a drug-induced liver injury (DILI). Delayed hepatotoxicity suggested a dose-dependency and a cumulative effect. The question of a common pathophysiology and a cross-toxicity was raised. Currently, 3% of DILI cases are associated with antimycotic agents. Nevertheless, only few case reports describe cross-toxicity or its absence after rechallenge with different azoles. The pathophysiology is not well understood. Ketoconazole was found to impair rat mitochondrial function in vitro. Further investigations showed cell membrane toxicity and ATP depletion in isolated human liver cancer cells. Interestingly, our patient carries a rare HLA B allele (HLA B 35*02), which occurs in less than 1% of the population and is known to be associated with minocycline-induced liver injury. Our case report suggests a cross-toxicity, dose-dependency and a possible genetic predisposition of triazole-induced liver injury.